Living Donor Advocacy An Evolving Role Within Transplantation - Steel Jennifer (Springer New York, 2014)
The inadequate supply of organs in the United States and other countries continues to drive the reliance on living donor transplantation.  Representatives of the transplant community convened for a meeting on living donation in an effort to provide guidelines to promote the welfare of living donors.  The consensus statement that resulted from this meeting recommended that transplant centers retain an Independent Living Donor Advocate (ILDA) to focus on the best interest of the donor.  Over a decade later, nearly every transplant center in the United States, performing living donor surgeries, has incorporated an ILDA into their living donor screening and/or evaluation process, however there are no guidelines with regard to the ILDA's qualifications, clinical practice, or how address ethical challenges.      Living Donor Advocacy is an overview of living donation and its risks, ethical challenges and future directions regarding this role within the transplantation process.  This book provides health care professionals or consumers of health care with information that facilitates their understanding of the complexity of the living donor surgeries and medical contraindications, evaluation of the donor, and bioethics involved in living donation.    Living Donor Advocacy brings the fragmented information in the literature together into a single, invaluable resource for health professionals and those undergoing transplantation or living donor surgery.